Manufacturing method of superabsorbent resin

A method for producing superabsorbent resin through polymerization and surface crosslinking with colloidal silica addresses the challenges of improving water absorption and preventing caking, resulting in enhanced performance and stability under high humidity conditions.

JP7601460B2Active Publication Date: 2024-12-17LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023537406
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2022-08-26
Publication Date
2024-12-17
Estimated Expiration
2042-08-26

AI Technical Summary

Technical Problem

Existing superabsorbent resins face challenges in achieving simultaneous improvement of water retention capacity and water absorption capacity under pressure, as well as issues with caking and reduced processability under high temperature/high humidity conditions.

Method used

A method involving photopolymerization or thermal polymerization of a monomer composition containing acrylic acid monomers, followed by mixing with colloidal silica, pulverization, drying, and surface crosslinking with colloidal or fumed silica to form a surface crosslinked layer, enhancing gel strength and preventing caking.

Benefits of technology

The method produces a superabsorbent resin with improved water absorption rate, anti-caking properties, and maintained water absorption properties, including high water retention capacity, pressurized water absorption capacity, and liquid permeability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601460000001
    Figure 0007601460000001
  • Figure 0007601460000002
    Figure 0007601460000002
Patent Text Reader

Abstract

The present invention relates to a method for producing a superabsorbent polymer. The method for producing a superabsorbent polymer of the present invention can provide a superabsorbent polymer that exhibits improved water absorption rate and anti-caking properties while maintaining excellent water absorption properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0120263 dated September 9, 2021 and Korean Patent Application No. 10-2022-0106810 dated August 25, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for producing a superabsorbent polymer, and more particularly to a method for producing a superabsorbent polymer that can exhibit improved water absorption rate and anti-caking properties. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb 500 to 1,000 times its own weight in water, and each developer has given it a different name, such as SAM (Super Absorbency Material), AGM (Absorbent Gel Material), etc. Such super absorbent polymers first came into practical use as sanitary products, and are now widely used in sanitary products such as baby diapers and sanitary napkins, as well as in soil water retention agents for gardening, water stoppers for civil engineering and construction, seedling sheets, freshness preserving agents in the food distribution field, and materials for compresses.

[0004] In most cases, such superabsorbent polymers are widely used in the field of sanitary materials such as diapers and sanitary napkins. For such applications, they must have high absorbency against moisture and the absorbed moisture must not escape even when subjected to external pressure. In addition, they must maintain their shape well even when they absorb water and expand in volume (swell), and exhibit excellent liquid permeability.

[0005] However, it is known that it is difficult to improve both the water retention capacity (CRC), which is a physical property indicating the basic water absorption and water retention of the superabsorbent polymer, and the water absorption capacity under pressure (AUP), which indicates the property of well retaining absorbed water even under external pressure. This is because when the overall crosslink density of the superabsorbent polymer is controlled to be low, the water retention capacity is relatively high, but the crosslinked structure becomes coarse and the gel strength is low, so the water absorption capacity under pressure may decrease. Conversely, when the crosslink density is controlled to be high to improve the water absorption capacity under pressure, the water is difficult to absorb between the dense crosslinked structure, so the basic water retention capacity may decrease. For the above reasons, there is a limit to providing a superabsorbent polymer with improved water retention capacity and water absorption capacity under pressure.

[0006] Recently, however, as sanitary materials such as diapers and sanitary napkins become thinner, there is a demand for higher water absorption performance from superabsorbent polymers. Among these, simultaneous improvement of the conflicting physical properties of water retention capacity and water absorption capacity under pressure, as well as improvement of liquid permeability, have emerged as important issues.

[0007] Furthermore, since the superabsorbent polymer is contained in sanitary materials such as diapers, it is often exposed to high temperature / high humidity conditions. However, when the superabsorbent polymer is exposed to high temperature / high humidity conditions, aggregation and / or caking between particles often occurs. When such aggregation and / or caking occurs, it may cause an increase in load during production and use, reducing processability, and may cause difficulties in using the superabsorbent polymer.

[0008] For this reason, attempts have been made to reduce caking between particles by treating the surfaces of superabsorbent resin particles with inorganic particles such as silica, but the technical requirements in this regard have not been fully met. Summary of the Invention [Problem to be solved by the invention]

[0009] In order to solve the problems of the prior art, the present invention aims to provide a method for producing a superabsorbent polymer that enables the production of a superabsorbent polymer that exhibits excellent water absorption performance, improved water absorption rate, and anti-caking properties. [Means for solving the problem]

[0010] In order to achieve the above object, according to one aspect of the present invention, forming a hydrogel polymer by photopolymerization or thermal polymerization of a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, an internal crosslinking agent, and a polymerization initiator; mixing colloidal silica with the hydrogel polymer and coarsely grinding the mixture; drying, grinding, and classifying the coarsely ground hydrogel polymer to form a base resin; and The method includes a step of further crosslinking the surface of the base resin in the presence of colloidal silica or fumed silica and a surface crosslinking agent to form a surface crosslinked layer. A method for producing a superabsorbent resin is provided. Effect of the Invention

[0011] According to the method for producing a superabsorbent polymer of the present invention, it is possible to provide a superabsorbent polymer that exhibits improved water absorption speed and anti-caking properties while maintaining various excellent water absorption properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Although the present invention can be implemented in various forms through various modifications, specific embodiments are described in detail below, but it is to be understood that this is not intended to limit the present invention to the specific disclosed embodiments, and that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0013] Hereinafter, a method for producing a highly water-absorbent resin according to one embodiment of the present invention will be described in detail.

[0014] A method for producing a superabsorbent resin according to one embodiment of the present invention includes the steps of: forming a hydrogel polymer by photopolymerization or thermal polymerization of a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, an internal crosslinking agent, and a polymerization initiator; mixing colloidal silica with the hydrogel polymer and coarsely grinding the mixture; drying, grinding, and classifying the coarsely ground hydrogel polymer to form a base resin; and The method includes a step of further cross-linking the surface of the base resin in the presence of either colloidal silica or fumed silica, and a surface cross-linking agent to form a surface cross-linked layer.

[0015] In the present specification, the term "base resin" or "base resin powder" refers to a polymer obtained by drying and pulverizing a polymer of an acrylic acid monomer into a particle or powder form, without undergoing a surface modification or surface crosslinking step described below.

[0016] The hydrous gel polymer obtained by the polymerization reaction of acrylic acid monomers is subjected to processes such as drying, pulverization, classification, and surface crosslinking, and is then commercially available as a powdered product called a highly water-absorbent resin.

[0017] Recently, in addition to the various water absorption properties such as water absorption capacity and liquid permeability, the extent to which the dryness of the swollen superabsorbent polymer surface can be maintained under the conditions in which the diaper is actually used has become an important measure of diaper properties. There are various factors that affect this dryness, but the gel deterioration phenomenon caused by ascorbic acid in urine has been pointed out as the main cause. In other words, ascorbic acid contained in urine reacts with the polymer structure of the superabsorbent polymer, decomposing the polymer structure and increasing the amount of water-soluble components, which causes the superabsorbent polymer or the diaper to become sticky, which is one of the main causes of the deterioration phenomenon.

[0018] Therefore, the inventors of the present invention have noticed that by mixing colloidal silica at the stage of coarsely pulverizing a polymer, the strength of the superabsorbent resin can be increased, and thus deterioration due to ascorbic acid can be effectively prevented, and have arrived at the present invention.

[0019] In addition, it was confirmed that by performing surface cross-linking in the presence of colloidal silica or fumed silica in the surface cross-linking step, it is possible to effectively prevent the caking phenomenon in which superabsorbent resin particles aggregate with each other in a high-temperature and high-humidity environment.

[0020] As a result, the superabsorbent resin obtained by the manufacturing method according to one embodiment of the present invention has excellent physical properties such as water retention capacity, pressurized water absorption capacity, liquid permeability, and water absorption speed, and can exhibit anti-caking effects.

[0021] This is explained in more detail below.

[0022] In the method for producing the superabsorbent resin of the present invention, first, a step of forming a hydrogel polymer by photopolymerization or thermal polymerization of a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, an internal crosslinking agent, and a polymerization initiator is performed.

[0023] The monomer composition, which is a raw material of the superabsorbent resin, includes an acrylic acid monomer having at least a partially neutralized acid group, an internal crosslinking agent, and a polymerization initiator.

[0024] The acrylic acid monomer is a compound represented by the following formula 1:

[0025] [C1] R 1 -COOM 1

[0026] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0027] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0028] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree can be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate, making it difficult to smoothly proceed with polymerization, and conversely, if the neutralization degree is too low, not only the water absorption of the polymer is greatly reduced, but also the polymer may exhibit properties similar to elastic rubber, which are difficult to handle.

[0029] The concentration of the acrylic acid monomer may be about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition containing the raw material of the superabsorbent resin and the solvent, and is set to an appropriate concentration in consideration of the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent resin may be low, which may cause problems in terms of economy, and conversely, if the concentration is too high, there may be process problems such as partial precipitation of the monomer or low pulverization efficiency during pulverization of the polymerized hydrogel polymer, which may result in a decrease in the physical properties of the superabsorbent resin.

[0030] In the method for producing a superabsorbent resin of the present invention, the polymerization initiator used during polymerization is not particularly limited as long as it is one that is generally used in the production of superabsorbent resins.

[0031] Specifically, the polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator by UV irradiation depending on the polymerization method. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet rays, etc., and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so a thermal polymerization initiator may also be included.

[0032] The photopolymerization initiator can be any compound capable of forming radicals by the action of light such as ultraviolet light, and is not limited in its composition.

[0033] The photopolymerization initiator may be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, as a specific example of acylphosphine, commercially available lucirin TPO, i.e., 2,4,6-trimethyl-benzoyl-trimethyl phosphine oxide, may be used. More various photoinitiators are well described in "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), p. 115, by Reinhold Schwalm, and are not limited to the above-mentioned examples.

[0034] The photopolymerization initiator is contained in a concentration of about 0.01 to about 1.0% by weight based on the monomer composition. If the concentration of the photopolymerization initiator is too low, the polymerization rate is slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin may be small, resulting in non-uniform physical properties.

[0035] In addition, the thermal polymerization initiator may be one or more selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate initiators include sodium persulfate (Na 2 S 2 O 8 ), potassium persulfate (K 2 S 2 O 8), Ammonium persulfate ((NH 4 ) 2 S 2 O 8 Examples of azo initiators include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, 2-(carbamoylazo)isobutylonitrile, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), A wide variety of thermal polymerization initiators are described in detail in "Principle of Polymerization" by Odian (Wiley, 1981), p. 203, and are not limited to the above-mentioned examples.

[0036] According to one embodiment of the present invention, the monomer composition includes an internal crosslinking agent as a raw material of the superabsorbent resin. The internal crosslinking agent may be a crosslinking agent having one or more functional groups capable of reacting with the acrylic acid monomer and one or more ethylenically unsaturated groups; or a crosslinking agent having two or more functional groups capable of reacting with the substituent of the acrylic acid monomer and / or the substituent formed by hydrolysis of the monomer.

[0037] Specific examples of the internal crosslinking agent include one or more selected from the group consisting of N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, ethylene glycol diglycidyl ether, propylene glycol, glycerin, and ethylene carbonate.

[0038] The internal crosslinking agent can be included in the monomer composition at a concentration of about 0.01 to about 0.5% by weight to crosslink the polymerized polymer.

[0039] In the production method of the present invention, the monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0040] Raw materials such as the acrylic acid-based monomer having the above-mentioned acidic groups, at least a portion of which is neutralized, the photopolymerization initiator, the thermal polymerization initiator, the internal crosslinking agent, and the additives are prepared in the form of a monomer composition solution dissolved in a solvent.

[0041] The solvent that can be used in this case is not limited in composition as long as it can dissolve the above-mentioned components. For example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide can be used in combination.

[0042] The solvent is contained in an amount remaining after excluding the above-mentioned components with respect to the total content of the monomer composition.

[0043] On the other hand, the method for forming a hydrogel polymer by thermal polymerization or photopolymerization of such a monomer composition is not particularly limited as long as it is a commonly used polymerization method.

[0044] Specifically, polymerization methods are broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Typically, thermal polymerization is carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization is carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.

[0045] For example, as described above, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft or by heating the reactor may have a shape of several centimeters to several millimeters when discharged from the outlet of the reactor, depending on the shape of the agitator shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer varies depending on the concentration of the monomer composition injected and the injection speed, but a hydrogel polymer having a weight average particle size of 2 to 50 mm is usually obtained.

[0046] In addition, when photopolymerization is carried out in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a sheet-like hydrogel polymer having the width of the belt. At this time, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition to be injected, but it is usually preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. When the monomer composition is supplied so that the thickness of the sheet-like polymer is excessively thin, the production efficiency is low, which is undesirable, and when the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction may not occur uniformly over the entire thickness due to the excessively thick thickness.

[0047] The water content of the hydrogel polymer obtained by this method may be about 40 to about 80% by weight. Meanwhile, throughout this specification, the "water content" refers to the water content relative to the total weight of the hydrogel polymer, and means the weight of the hydrogel polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer by infrared heating. Here, the drying conditions are a method of increasing the temperature to about 180°C at room temperature and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase stage, and the water content is measured.

[0048] Next, the hydrogel polymer is mixed with colloidal silica and coarsely pulverized.

[0049] The colloidal silica means silica in a state where silica particles are stably dispersed in water without being precipitated or aggregated, and means silica in which at least a part of the surface of the silica particles is ionized. The method for producing the colloidal silica is not particularly limited, and colloidal silica produced by known production methods such as electrodialysis, sol-gel method, ion exchange method, acid-neutralization method, etc. can be used.

[0050] The colloidal silica is added in an amount of 0.01 parts by weight or more, or 0.02 parts by weight or more, or 0.03 parts by weight or more, or 0.05 parts by weight or more, or 0.08 parts by weight or more, or 0.1 parts by weight or more and 1.0 parts by weight or less, or 0.8 parts by weight or less, or 0.5 parts by weight or less, or 0.2 parts by weight or less, based on 100 parts by weight of the hydrogel polymer. When the content of the colloidal silica is within the above range, it is possible to achieve an effect of improving gel strength without decreasing the water absorption properties of the superabsorbent resin, and from this viewpoint, it is preferable to use it within the above range of parts by weight.

[0051] In addition, if the colloidal silica cannot maintain a colloidal state and precipitates during the process of coarsely grinding the colloidal silica together with the hydrogel polymer, the gel strength improving effect cannot be obtained, so it is preferable to use colloidal silica that maintains a stable colloidal state. From this perspective, powdered silica or hydrophobic silica that is not in a colloidal state does not have the effect of improving the gel strength, and the intended effect of the present invention cannot be achieved.

[0052] Examples of colloidal silica that meets these conditions include Nissan Chemical Company's ST-30, ST-O, ST-N, ST-C, and ST-AK, but the present invention is not limited to these.

[0053] According to the production method of the present invention, such colloidal silica is added during coarse grinding and coarse grinding is carried out in the presence of the colloidal silica, whereby the hydrogel polymer and the colloidal silica are uniformly mixed and distributed, thereby providing an effect of improving the gel strength of the hydrogel polymer, and this effect is maintained in the base resin and the final superabsorbent resin, thereby improving the deterioration phenomenon caused by ascorbic acid.

[0054] The crusher used in the coarse crushing step is not limited in configuration, and specifically may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.

[0055] In this case, the coarse pulverization step can be carried out so that the hydrogel polymer has a particle size of about 2 to about 10 mm.

[0056] Grinding to a particle size of less than 2 mm is technically difficult due to the high water content of the hydrous gel polymer, and the crushed particles may aggregate with each other. On the other hand, grinding to a particle size of more than 10 mm has little effect on increasing the efficiency of the subsequent drying step.

[0057] The coarsely ground hydrogel polymer is then dried, ground, and classified to form a base resin.

[0058] The drying temperature in the drying step may be about 150 to about 250° C. If the drying temperature is less than 150° C., the drying time becomes too long, and the physical properties of the finally formed superabsorbent resin may be deteriorated, and if the drying temperature exceeds 250° C., only the polymer surface may be dried excessively, and fine powder may be generated in the subsequent pulverization process, and the physical properties of the finally formed superabsorbent resin may be deteriorated. Therefore, the drying is preferably performed at a temperature of about 150 to about 200° C., more preferably at a temperature of about 160 to about 180° C.

[0059] Meanwhile, the drying time is about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0060] The drying method in the drying step can be selected and used without any limitation on the configuration as long as it is one that is usually used in the drying process of hydrous gel polymers. Specifically, the drying step can be carried out by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such drying step may be about 0.1 to about 10% by weight.

[0061] The dried polymer obtained after such a drying step is then pulverized.

[0062] The pulverization is carried out so that the particle size of the polymer powder obtained after the pulverization step is 150 to 850 μm. Specifically, the pulverizer used for pulverizing to have such a particle size may be a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, or a jog mill, but the present invention is not limited to the above examples.

[0063] After the pulverization step, in order to control the physical properties of the superabsorbent resin powder that is finally manufactured, the polymer powder obtained after pulverization may be classified according to particle size, and the polymer powder may be classified to have a certain weight ratio according to the particle size range.

[0064] The classification step may be carried out by a conventional method, such as using a standard sieve according to ASTM regulations, and such a classification step can separate and remove fine particles having a particle size of less than 150 μm and coarse particles having a particle size of more than 850 μm, thereby obtaining normal particles of the superabsorbent resin having a size of 150 to 850 μm.

[0065] The polymer obtained by polymerizing the acrylic acid monomer in the above-mentioned process is dried and pulverized into particles or powder, which is called a base resin.

[0066] The base resin of the present invention produced as described above may have a water retention capacity (CRC) as measured by EDANA method WSP241.3 in the range of 45 g / g or more, or 50 g / g or more, or 51 g / g or more, or 52 g / g or more, and 60 g / g or less, or 58 g / g or less, or about 55 g / g or less.

[0067] Although the water retention capacity (CRC) of the base resin inevitably decreases during the surface cross-linking reaction stage described below, according to the present invention, the water retention capacity of the base resin is made high, so that the water retention capacity of the final product can be maintained high.

[0068] In addition, the base resin of the present invention can have a high gel strength range, as measured by a tensile / compression test method, of 0.1 N or more, or 0.12 N or more, or 0.14 N or more, or 0.15 N or more, and 0.20 N or less, or 0.19 N or less, or 0.18 N or less.

[0069] Next, a step of forming a surface cross-linked layer is carried out by additionally cross-linking the surface of the base resin in the presence of either colloidal silica or fumed silica and a surface cross-linking agent.

[0070] In a general method for producing a superabsorbent resin, a surface crosslinking solution containing a surface crosslinking agent is mixed with a dried and pulverized polymer, i.e., a base resin, and then the mixture is heated to increase the temperature, thereby carrying out a surface crosslinking reaction on the pulverized polymer.

[0071] The surface cross-linking step is a step of forming a superabsorbent resin having improved physical properties by inducing a cross-linking reaction on the surface of the pulverized polymer in the presence of a surface cross-linking agent. By such surface cross-linking, a surface cross-linked layer (surface modified layer) is formed on the surface of the pulverized base resin.

[0072] Generally, the surface cross-linking agent is applied to the surface of the superabsorbent polymer particles, so that the surface cross-linking reaction occurs on the surface of the superabsorbent polymer particles, which improves the cross-linking property on the surface of the particles without substantially affecting the interior of the particles. Thus, the surface cross-linked superabsorbent polymer particles have a higher degree of cross-linking near the surface than in the interior.

[0073] According to the manufacturing method of the present invention, in the step of mixing a surface cross-linking agent into a base resin and performing a surface cross-linking reaction, hydrophobic silica such as colloidal silica or fumed silica is additionally mixed to perform the surface cross-linking reaction. As a result, colloidal silica or fumed silica is included in the cross-linked structure on the surface cross-linked layer, improving the surface cross-linking efficiency, and the permeability can be further improved compared to a superabsorbent resin that does not use this. In addition, the caking phenomenon in which superabsorbent resin particles aggregate with each other in a high temperature and high humidity environment can be effectively prevented.

[0074] More specifically, the colloidal silica or fumed silica is distributed in the surface modification layer on the surface of the base resin, and prevents the swollen resin particles from agglomerating or clumping together due to the increased pressure during the process in which the superabsorbent resin absorbs liquid and swells, and imparts suitable hydrophobicity to the surface, making it easier for liquid to permeate and diffuse, thereby contributing to improving the water absorption speed, liquid permeability, and anti-caking properties of the superabsorbent resin.

[0075] Examples of the colloidal silica include ST-30, ST-O, ST-N, ST-C, and ST-AK manufactured by Nissan Chemical Co., Ltd., but the present invention is not limited thereto.

[0076] The fumed silica may be, for example, commercially available silica such as Aerosil, Tixosil, or DM30S, but the present invention is not limited thereto.

[0077] The colloidal silica or fumed silica is added in an amount of 0.01 parts by weight or more, or 0.02 parts by weight or more, or 0.03 parts by weight or more, or 0.05 parts by weight or more, or 0.08 parts by weight or more, or 0.1 parts by weight or more and 1.0 parts by weight or less, or 0.8 parts by weight or less, or 0.5 parts by weight or less, or 0.2 parts by weight or less, relative to 100 parts by weight of the base resin. When the content of the colloidal silica or fumed silica is within the above-mentioned range, it is possible to achieve liquid permeability and caking prevention effects without decreasing the water absorption properties of the superabsorbent resin, and from this viewpoint, the above-mentioned range of parts by weight is preferable.

[0078] The method of mixing the colloidal silica or fumed silica is not particularly limited as long as the method can uniformly mix the colloidal silica or fumed silica with the base resin, and any method can be appropriately adopted and used.

[0079] For example, the colloidal silica or fumed silica may be mixed in a dry manner before mixing the base resin with a surface cross-linking solution containing a surface cross-linking agent, or may be dispersed in the surface cross-linking solution and then mixed with the base resin together with the surface cross-linking solution.

[0080] When the surface crosslinking agent is added, water may be added in the form of a surface crosslinking solution by additionally mixing the agent with water. When water is added, the surface crosslinking agent can be uniformly dispersed in the polymer. At this time, the content of the added water is preferably about 1 to about 10 parts by weight per 100 parts by weight of the base resin in order to induce uniform dispersion of the surface crosslinking agent, prevent clumping of the polymer powder, and optimize the surface penetration depth of the surface crosslinking agent.

[0081] The surface cross-linking agent is not limited in terms of its constitution as long as it is a compound capable of reacting with the functional group of the polymer.

[0082] Preferably, in order to improve the properties of the resulting superabsorbent resin, the surface crosslinking agent can be one or more selected from the group consisting of polyhydric alcohol compounds; epoxy compounds; polyamine compounds; haloepoxy compounds; condensation products of haloepoxy compounds; oxazoline compounds; mono-, di- or polyoxazolidinone compounds; cyclic urea compounds; polyvalent metal salts; and alkylene carbonate compounds.

[0083] Specifically, examples of the polyhydric alcohol compound that can be used include one or more selected from the group consisting of mono-, di-, tri-, tetra- or polyethylene glycol, monopropylene glycol, 1,3-propanediol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,2-cyclohexanedimethanol.

[0084] In addition, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetetraamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and polyamidepolyamine can be used.

[0085] As the haloepoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, while as the mono-, di-, or polyoxazolidinone compound, for example, 2-oxazolidinone can be used.

[0086] As the alkylene carbonate compound, ethylene carbonate or the like can be used. These may be used alone or in combination with each other. On the other hand, in order to increase the efficiency of the surface cross-linking step, one or more polyhydric alcohol compounds having 2 to 10 carbon atoms can be included in these surface cross-linking agents and used.

[0087] The content of the surface crosslinking agent to be added can be appropriately selected depending on the type of the surface crosslinking agent to be added and the reaction conditions, and it can usually be used in an amount of 0.001 to 5 parts by weight, preferably 0.01 to 3 parts by weight, and more preferably 0.05 to 2 parts by weight, relative to 100 parts by weight of the base resin.

[0088] If the content of the surface cross-linking agent is too low, the surface cross-linking reaction hardly occurs, whereas if the content exceeds 5 parts by weight per 100 parts by weight of the base resin, the surface cross-linking reaction proceeds excessively, which may result in a decrease in water absorption capacity and physical properties.

[0089] On the other hand, in addition to the above-mentioned surface crosslinking agent, a polyvalent metal salt, for example, an aluminum salt, more specifically, one or more selected from the group consisting of an aluminum sulfate salt, a potassium salt, an ammonium salt, a sodium salt, and a hydrochloride salt, may be further included.

[0090] By additionally using such a polyvalent metal salt, the liquid permeability of the superabsorbent resin produced by the method of one embodiment can be further improved. Such a polyvalent metal salt may be added to the surface crosslinking solution together with the surface crosslinking agent, and may be used in an amount of 0.01 to 4 parts by weight based on 100 parts by weight of the base resin.

[0091] The step of forming a surface cross-linked layer by additionally cross-linking the surface of the base resin is carried out by applying heat to the mixture of the colloidal silica or fumed silica, the base resin, and the surface cross-linking agent to raise the temperature.

[0092] The temperature increase can be carried out by heating for about 10 to about 90 minutes, preferably about 20 to about 70 minutes, at a temperature of about 80 to about 190° C., preferably about 100 to about 180° C., more preferably about 110 to about 140° C. If the crosslinking reaction temperature is too low or the reaction time is too short, the surface crosslinking reaction does not proceed well, resulting in low permeability, whereas if the temperature is too high or the reaction time is too long, a problem of reduced water retention may occur.

[0093] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but the present invention is not limited thereto, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, the heat source to be directly supplied can be exemplified by heating by electricity and heating by gas, but the present invention is not limited to the above-mentioned examples.

[0094] According to the production method of the present invention, the colloidal silica added during coarse pulverization gives the base resin excellent gel strength, and the colloidal silica or fumed silica added in the surface crosslinking stage forms a surface crosslinked layer in which silica is distributed within the surface crosslinked structure.

[0095] Therefore, the superabsorbent resin produced by the production method of the present invention can have improved water absorption speed, liquid permeability, and anti-caking properties without decreasing physical properties such as water retention capacity and pressurized water absorption capacity due to the characteristics of the base resin and the surface cross-linked layer formed on the base resin.

[0096] Therefore, the superabsorbent polymer produced by the manufacturing method of the present invention can have a water retention capacity (CRC) of the superabsorbent polymer measured by EDANA method WSP241.3 of 35 g / g or more, or 36 g / g or more, or 37 g / g or more, and 45 g / g or less, or 43 g / g or less, or 40 g / g or less.

[0097] In addition, the superabsorbent resin produced by the production method of the present invention may have an absorbency under pressure (AUP) at 0.7 psi, as measured by EDANA method WSP242.3, in the range of 20 g / g or more, or 21 g / g or more, and 30 g / g or less, or 28 g / g or less, or 26 g / g or less.

[0098] Furthermore, the superabsorbent resin produced by the production method of the present invention may have a water absorption speed (vortex time) by a vortex method of 45 seconds or less, 43 seconds or less, 42 seconds or less, or 41 seconds or less. The smaller the value of the water absorption speed, the better, and the lower limit of the water absorption speed is theoretically 0 seconds, but for example, it may be 5 seconds or more, 10 seconds or more, or 20 seconds or more.

[0099] The water absorption rate refers to the time (unit: seconds) required for liquid vortexes to disappear due to rapid water absorption when a superabsorbent polymer is added to saline and stirred. The shorter the time, the faster the initial water absorption rate of the superabsorbent polymer is.

[0100] The superabsorbent resin produced by the production method of the present invention may have a liquid permeability (unit: seconds) of 50 seconds or less, 48 ​​seconds or less, 46 seconds or less, or 45 seconds or less. The smaller the value of the liquid permeability, the better it is, and the theoretical upper and lower limits are 0 seconds, but it may be, for example, 10 seconds or more, 20 seconds or more, or 30 seconds or more.

[0101] The method for measuring the liquid permeability will be explained in more detail in the examples described below.

[0102] In addition, the superabsorbent resin produced by the production method of the present invention may have an anti-caking efficiency of 88.0% or more, or 88.5% or more, or 89.0% or more, or 89.5% or more, and 95.0% or less, or 94.0% or less, or 93.0% or less, or 92.0% or less.

[0103] The method for measuring the anti-caking efficiency will be explained in more detail in the Examples below.

[0104] Furthermore, the superabsorbent resin produced by the production method of the present invention can have a high gel strength range, as measured by a tensile / compression test method, of 0.70 N or more, or 0.72 N or more, or 0.74 N or more, or 0.75 N or more, and 0.90 N or less, or 0.85 N or less, or 0.80 N or less.

[0105] The method for measuring the gel strength will be explained in more detail in the Examples below.

[0106] Furthermore, the superabsorbent resin produced by the production method of the present invention satisfies at least one, preferably two or more of the above-described physical property ranges of water retention capacity (CRC), 0.7 psi absorbency (AUP), water absorption rate (vortex time), liquid permeability, anti-caking efficiency, and gel strength, and more preferably satisfies all of the physical property ranges simultaneously.

[0107] As described above, the superabsorbent resin of the present invention has excellent water absorption capacity, and can exhibit improved water absorption rate, liquid permeability, and anti-caking properties.

[0108] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0109] <Example> Manufacture of superabsorbent polymers Example 1 In a 2L glass container equipped with a stirrer and a thermometer, 507.8g of acrylic acid, 0.3g of ethylene glycol diglycidyl ether (EGDGE) as an internal crosslinking agent, 0.04g of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide as a photoinitiator, 0.76g of sodium persulfate (SPS) as a thermal initiator, 627.1g of 31.5% sodium hydroxide solution, 0.51g of sodium dodecyl sulfate (SDS) as a surfactant, and 238.7g of distilled water were mixed to prepare a water-soluble unsaturated monomer aqueous solution (neutralization degree: 70 mol%; solid content: 41 wt%).

[0110] Thereafter, when the temperature of the monomer aqueous solution reached 43°C, it was irradiated with ultraviolet light for 1 minute (irradiation dose: 10 mW / cm 2) and UV polymerization was carried out, and the mixture was maintained in the polymerization vessel for 2 minutes to obtain a hydrogel polymer. 0.1 parts by weight of colloidal silica was added to 100 parts by weight of the obtained hydrogel polymer, and the mixture was crushed to a size of 2 mm x 2 mm. The water content (dried at 180 degrees for 40 minutes) was measured and found to be 53%.

[0111] The obtained hydrogel polymer was spread to a thickness of about 30 mm on a stainless steel wire gauze having a hole size of 600 μm, and dried for 30 minutes in a hot air oven at 180° C. The dried polymer thus obtained was pulverized using a pulverizer and classified using a standard mesh sieve according to the ASTM standard to obtain a base resin having a particle size of 150 to 850 μm.

[0112] Thereafter, a surface treatment solution containing 5.8 parts by weight of water, 3 parts by weight of methanol, 0.5 parts by weight of propylene glycol, 0.1 parts by weight of ethylene glycol diglycidyl ether (EGDGE), and 0.05 parts by weight of colloidal silica was uniformly mixed with respect to 100 parts by weight of the prepared base resin, and then the mixture was supplied to one surface crosslinking reactor, where the surface crosslinking reaction of the base resin was carried out at 130°C for 40 minutes.

[0113] After the surface treatment was completed, a surface-treated superabsorbent resin having an average particle size of 150 to 850 μm was obtained using a sieve.

[0114] Example 2 A highly water-absorbent resin was produced in the same manner as in Example 1, except that 0.05 parts by weight of fumed silica was added instead of colloidal silica during surface cross-linking.

[0115] Example 3 A highly water-absorbent resin was produced in the same manner as in Example 1, except that 0.03 part by weight of colloidal silica was added during surface cross-linking.

[0116] Example 4 A highly water-absorbent resin was produced in the same manner as in Example 1, except that 0.1 parts by weight of colloidal silica was added during surface cross-linking.

[0117] Example 5 A highly water-absorbent resin was produced in the same manner as in Example 2, except that 0.03 parts by weight of fumed silica was added during surface cross-linking.

[0118] Example 6 A highly water-absorbent resin was produced in the same manner as in Example 2, except that 0.1 parts by weight of fumed silica was added during surface cross-linking.

[0119] Comparative Example 1 A highly water-absorbent resin was produced in the same manner as in Example 1, except that colloidal silica was not added during the coarse pulverization.

[0120] Comparative Example 2 A highly water-absorbent resin was produced in the same manner as in Example 2, except that colloidal silica was not added during the coarse pulverization.

[0121] Comparative Example 3 A superabsorbent resin was produced in the same manner as in Example 1, except that, instead of adding colloidal silica during coarse pulverization in Example 1, 0.1 parts by weight of colloidal silica was added to 100 parts by weight of neutralized acrylic acid in the monomer composition, polymerization was allowed to proceed, and no colloidal silica was added during surface crosslinking.

[0122] Comparative Example 4 A superabsorbent resin was produced in the same manner as in Example 1, except that, instead of adding colloidal silica during coarse pulverization in Example 1, 0.1 parts by weight of fumed silica was added to 100 parts by weight of neutralized acrylic acid in the monomer composition, polymerization was allowed to proceed, and no colloidal silica was added during surface crosslinking.

[0123] Comparative Example 5 A highly water-absorbent resin was produced in the same manner as in Example 1, except that colloidal silica was not added during surface cross-linking.

[0124] Comparative Example 6 A superabsorbent resin was produced in the same manner as in Example 1, except that in Example 1, 0.1 parts by weight of fumed silica was added per 100 parts by weight of the hydrogel polymer instead of colloidal silica during coarse pulverization, and no colloidal silica was added during surface crosslinking.

[0125] Comparative Example 7 A highly water-absorbent resin was produced in the same manner as in Example 1, except that 0.1 parts by weight of fumed silica was added per 100 parts by weight of the hydrous gel polymer instead of colloidal silica during coarse pulverization.

[0126] Comparative Example 8 A superabsorbent resin was produced in the same manner as in Example 1, except that in Example 1, 0.1 parts by weight of fumed silica was added per 100 parts by weight of the hydrous gel polymer instead of colloidal silica during coarse pulverization, and 0.05 parts by weight of fumed silica was added per 100 parts by weight of the base resin during surface crosslinking.

[0127] The conditions for adding silica in the above examples and comparative examples are summarized in Table 1 below.

[0128] [Table 1]

[0129] <Experimental Example> The superabsorbent resins prepared in the above Examples and Comparative Examples were evaluated for physical properties by the following methods.

[0130] Unless otherwise indicated, all of the following physical property evaluations were performed at constant temperature and humidity (23±1°C, relative humidity 50±10%), and saline or salt water refers to a 0.9 wt% aqueous sodium chloride (NaCl) solution.

[0131] Unless otherwise specified, the physical properties of the base resin before surface crosslinking were evaluated using a resin having a particle size of 300 μm to 600 μm classified using an ASTM sieve, and the physical properties of the final surface-crosslinked superabsorbent resin were evaluated using a resin having a particle size of 150 μm to 850 μm classified using an ASTM sieve.

[0132] (1)Centrifuge Retention Capacity (CRC) The water retention capacity of each resin was measured using EDANA WSP241.3, based on the water absorption capacity under no load.

[0133] Specifically, the highly water-absorbent resin W 0 (g) (about 0.2 g) was uniformly placed in a nonwoven envelope, sealed, and then immersed in physiological saline (0.9 wt%) at room temperature. After 30 minutes, the water was removed from the envelope at 250 G for 3 minutes using a centrifuge, and the mass of the envelope W 2 The mass W (g) was measured after the same procedure was performed without using the resin. 1 The CRC (g / g) was calculated using the obtained masses according to the following formula:

[0134] [Formula 1] CRC(g / g) = {[W 2 (g)-W 1 (g)] / W 0 (g)}-1

[0135] (2) Absorbency under Pressure (AUP) The water absorption capacity of each resin at 0.7 psi was measured by EDANA method WSP242.3.

[0136] Specifically, a 400-mesh stainless steel wire net was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. 0 The piston that can uniformly spread the powder (0.9g) and apply a load of 0.7 psi evenly on it is slightly smaller than 60 mm in outer diameter, has no gap with the inner wall of the cylinder, and is designed so that the up and down movement is not hindered. At this time, the weight W 3 (g) was measured.

[0137] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and physiological saline consisting of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper, and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted up and its weight W 4 (g) was measured.

[0138] Using the obtained masses, the water absorption capacity under pressure (g / g) was calculated according to the following formula.

[0139] [Formula 2] AUP(g / g) = [W 4 (g)-W 3 (g)] / W 0 (g)

[0140] (3) Permeability The permeability was measured according to the method described in US Pat. No. 9,656,242 B2.

[0141] The liquid permeability measuring device is a chromatography tube with an inner diameter of 20 mm and a glass filter attached to the bottom. Lines were displayed on the liquid levels of 20 ml and 40 ml when a piston was inserted into the chromatography tube. After this, water was poured in reverse to fill the tube to about 10 ml, taking care not to create air bubbles between the glass filter at the bottom of the chromatography tube and the stopcock, and the tube was washed with salt water 2 to 3 times, and then filled with 0.9% salt water until the liquid level reached 40 ml or more. The piston was inserted into the chromatography tube, the bottom valve was opened, and the time (B) for the liquid level to decrease from 40 ml to the 20 ml display line was recorded.

[0142] 10 ml of salt water was left in the chromatography tube, 0.2±0.0005 g of classified (300μm~600μm) superabsorbent polymer sample was added, salt water was added to make the volume of salt water 50 ml, and then it was left for 30 minutes. After that, a piston (0.3 psi=106.26 g) was further added to the chromatography tube and left for 1 minute, and then the lower valve of the chromatography tube was opened, and the time (T1) for the liquid level to decrease from 40 ml to the 20 ml mark was recorded, and the time (unit: seconds) for T1-B was calculated.

[0143] (4) Water absorption rate (Vortex time) The vortex time was measured in seconds according to the method described in WO 1987 / 003208.

[0144] Specifically, 2 g of superabsorbent resin was placed in 50 mL of saline solution at 23°C to 24°C, and the solution was stirred at 600 rpm with a magnetic bar (diameter 8 mm, length 30 mm), and the time until the vortex disappeared was measured in seconds.

[0145] (5) Anti-caking efficiency The weight of a 9 cm diameter Petri dish was precisely weighed and recorded (W1). 2±0.01 g of superabsorbent polymer sample was precisely weighed and evenly spread on the Petri dish, and the Petri dish was left for 10 minutes in a temperature and humidity chamber set at 40°C and 80%RH. After 10 minutes, the Petri dish was taken out, turned upside down on an A4 sheet of paper, and left for 5 minutes. After 5 minutes, the weight of the sample that had fallen to the bottom (S1) and the weight of the Petri dish (S2) were precisely weighed and recorded. The measured values ​​were used to calculate the anti-caking efficiency (A / C efficiency) according to the following Equation 3.

[0146] [Formula 3] Anti-caking efficiency (%) = [S1 / (S2-W1)+S1] x 100

[0147] (6) Gel strength A 100-ml beaker was filled with 2.5±0.01 g of superabsorbent polymer sample, which was then uniformly dispersed. 50 ml of a mixture of physiological saline (0.9 wt% salt water) and ascorbic acid dissolved at a concentration of 0.005 wt% was added. The beaker containing the swollen superabsorbent polymer was wrapped in plastic wrap and placed in an oven set at 40°C for 24 hours to degrade. After 24 hours, the beaker was removed and placed on a stand for measuring gel strength (FGS-50E-H, SHIMPO, Japan), and pressure was applied to the swollen superabsorbent polymer in the beaker using a tensile / compression tester (FGP-2, SHIMPO, Japan) attached to the stand. The value displayed on the tensile / compression tester was recorded as the gel strength.

[0148] The physical properties of the above examples and comparative examples are shown in Table 2 below.

[0149] [Table 2]

[0150] Referring to Table 2, it was confirmed that all of Examples 1 to 6 of the present invention exhibited high gel strength, excellent water absorption properties, water absorption speed, liquid permeability, and anti-caking efficiency.

[0151] In contrast, Comparative Examples 1 to 4, in which colloidal silica was not added during coarse pulverization, exhibited low gel strength and anti-caking efficiency, and in addition, the liquid permeability was also inferior to that of the Examples.

[0152] In Comparative Example 5, silica was not added during surface cross-linking, and the liquid permeability and anti-caking efficiency were low. In Comparative Examples 6 to 8, fumed silica was added instead of colloidal silica during coarse pulverization, and the gel strength and liquid permeability were low.

Claims

1. forming a hydrogel polymer by photopolymerization or thermal polymerization of a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, an internal crosslinking agent, and a polymerization initiator; mixing colloidal silica with the hydrogel polymer and coarsely grinding the mixture; drying, grinding, and classifying the coarsely ground hydrogel polymer to form a base resin; and The method includes the step of further cross-linking the surface of the base resin in the presence of colloidal silica or fumed silica and a surface cross-linking agent to form a surface cross-linked layer; The water retention capacity (CRC) of the superabsorbent resin measured by EDANA method WSP241.3 is 35 g / g or more. A method for producing a superabsorbent resin.

2. 2. The method for producing a highly water-absorbent resin according to claim 1, wherein in the step of mixing the hydrogel polymer with colloidal silica and coarsely pulverizing the mixture, the colloidal silica is contained in an amount of 0.01 to 1.0 part by weight per 100 parts by weight of the hydrogel polymer.

3. 3. The method for producing a superabsorbent resin according to claim 1, wherein in the step of forming a surface cross-linked layer by additionally cross-linking the surface of the base resin, the colloidal silica or fumed silica is contained in an amount of 0.01 to 1.0 part by weight based on 100 parts by weight of the base resin.

4. The method for producing a highly water-absorbent resin according to claim 1, wherein the base resin has a gel strength of 0.1 N or more as measured by a tensile / compression test method.

5. The base resin has a water retention capacity (CRC) of 45 g / g or more as measured by EDANA method WSP241.

3. A method for producing the highly water-absorbent resin according to claim 1.

6. The superabsorbent resin has an absorbency under pressure (AUP) of 20 g / g or more at 0.7 psi as measured by EDANA method WSP242.

3. A method for producing the highly water-absorbent resin according to claim 1.

7. The method for producing a superabsorbent polymer according to claim 1, wherein the superabsorbent polymer has a liquid permeability (unit: second) of 50 seconds or less.

8. The superabsorbent resin has a water absorption speed (vortex time) of 45 seconds or less when measured by a vortex method. A method for producing the highly water-absorbent resin according to claim 1.

9. The superabsorbent resin has an anti-caking efficiency of 88.0% or more. A method for producing the highly water-absorbent resin according to claim 1.

10. The superabsorbent resin has a gel strength of 0.70 N or more as measured by a tensile / compression test method. A method for producing the highly water-absorbent resin according to claim 1.

Citation Information

Patent Citations

  • Refrigerator

    JP1989057067A

  • Highly water-absorbent resin and method for producing the same

    JP2021517603A

  • Method for producing super absorbent polymer

    WO2021071246A1